mTADA is a framework for identifying risk genes from de novo mutations in multiple traits - Tan-Hoang Nguyen (Nature Portfolio, 2020)
Joint analysis of multiple traits can increase power and provide insights into shared genetic architecture. Here, Nguyen et al. develop multi-trait TADA (mTADA), an extension of TADA (transmission and de novo association test) that jointly analyses de novo mutations of traits for improved risk-gene identification power.